2020
DOI: 10.3892/ijmm.2020.4738
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa aqueous extract: A potential solution for the prevention of corneal scarring as a result of pterygium surgical excision (Review)

Abstract: curcumin has been used since ancient times as a treatment for a wide range of pathologies. For centuries, it has been considered to be an effective aid for common human diseases. Curcuma longa has been reported to possess various beneficial properties and actions, including anti-inflammatory, proapoptotic, antiangiogenic and cortisone-like actions. Pterygium is a degenerative disorder of the conjunctiva indicative of a strong inflammatory condition that requires surgical treatment, which often results in disfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…tolerate up to a dose of 8000 mg per day. (Dorota et al, 2019;Stati et al, 2020) Curcumin belongs to the group of natural antioxidants. The effect of curcumin on free radicals is carried out by several different mechanisms.…”
Section: Therapymentioning
confidence: 99%
“…tolerate up to a dose of 8000 mg per day. (Dorota et al, 2019;Stati et al, 2020) Curcumin belongs to the group of natural antioxidants. The effect of curcumin on free radicals is carried out by several different mechanisms.…”
Section: Therapymentioning
confidence: 99%
“…These treatments have not led to a consistent reduction in the relapse cases. Several research groups reported a different percentage of relapses, corneal scarring and side effects respectively, due to surgical procedure and drugs utilized [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%